Jumlah Kepala Sekolah Dan Guru Menurut Kelompok Umur Provinsi Sumatera Utara, Jawa Tengah, Kalimantan Tengah Dan Sulawesi Tengah Tahun 2023/2024 - Mabi Palaka, Muhammad; Pratama Ramadhan, Ariyas; Raffi, Muhammad; Rosyani, Perani (CV. Shofanah Media Berkah, 2024)
This study aims to evaluate educational practices based on population density in four provinces in Indonesia: North Sumatra, Central Java, Central Kalimantan, and Central Sulawesi. Age grouping is done using a method called Biner. This is intended to display data in a more interactive and informative graphical style such as histograms, polygons, and ogives. This method was chosen because it can transform traditional data visualization into something that is easier to understand and interesting. Through graphical analysis, the results of the study show that there are significant differences in the number of teaching staff across the states. Central Kalimantan Province has the largest number of students, while Central Java Province has the largest number of students compared to any region in the country. This study using the Binner method contributes to a deeper understanding of the distribution of democratic power in education. This is expected to be a pillar of education.